Innovation Strategies of Private Madrasah Aliyah Principals in Realizing Sustainable Education - Marliat, Marliat; Harto, Kasinyo; Abdurrahmansyah, Abdurrahmansyah; Hamidah, Hamidah; Wigati, Indah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the innovation strategies of private Madrasah Aliyah principals in realizing sustainable education. The study uses a qualitative approach with a phenomenological method to understand the experiences and leadership practices of madrasah principals in designing and implementing educational innovations. The research was conducted at three private Islamic high schools, namely MAS Nurul Huda Sukaraja, MAS Al-Ikhlas Pametung Basuki, and MAS YPI Sumberharjo in Ogan Komering Ulu Timur Regency, South Sumatra Province, which were selected purposively based on the sustainability of innovation programs and the active involvement of madrasah principals in policy-making. The research data consisted of the innovation strategies of private Madrasah Aliyah principals in realizing sustainable education, which included academic innovation, religious innovation, and vocational innovation, as well as the leadership experiences of madrasah principals in designing and implementing these strategies. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies, and then analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the madrasah principals' innovation strategies were developed through three main orientations, namely academic innovation, religious innovation, and vocational innovation. Academic innovation focuses on improving the quality of learning and the continuity of graduates' studies to higher education, religious innovation is directed at strengthening Islamic values and the social role of alumni, while vocational innovation emphasizes the development of life skills to increase the independence and competitiveness of graduates in the world of work. These three strategies are implemented contextually in accordance with the characteristics of the madrasah and the needs of the environment. This study concludes that the innovation strategies of private Madrasah Aliyah principals contribute significantly to the realization of sustainable education, thus emphasizing the importance of innovative leadership in the development of Islamic education that is adaptive and relevant to the demands of the times.